(untitled) (Global Journal of Science Frontier Research, 2012)
This study was carried out during two successive seasons 2007 and 2008 on 25 years old Washington Navel orange trees Citrus sinensis L.; budded on sour orange root stock growing in a private orchard. To study influence of reducing herbicides rates in Washington Navel orange trees. The present investigation covered the effect of some herbicides with two rates for each (recommended dose and half of recommended dose + 4Kg urea /fed) as well as hand hoeing on controlling weeds spread in citrus orchard. There was a significant depression in fresh weight of grass, broad leaved and total weeds with hand hoeing and herbicides treatments (Touchdown, Fluazifop-butyl and Pendimethalin with recommended and half recommended dose + 4Kg urea/fed) when compared with unweeded treatment. the urea to a half recommended dose of herbicides gave the same effect of the recommended dose of herbicides to broad -leaved and grass weeds in citrus orchard and none showed any phylotoxic effect on the foliage of citrus plants. Pendimethalin IL + 4 Kg urea / fed treatment gave the highest yield / tree when compared with other herbicides treatments.